SEQUENCE ANALYSIS AND IDENTIFICATION OF COPPER BINDING RESIDUES IN SELECTED FUNGAL LACCASE INVOLVED IN LIGNOCELLULOSE WASTE MATERIAL DEGRADATION - P.U.MAHALINGAM; P.PANDI; N.ARUMUGAM (International Journal of Pharma and Bio Sciences, 2012)
Microbial degradation of cellulose and lignocelluloses derivatives has received considerable attention towards bioremediation in recent years. The biological significance of lignin combined with the commercial utility of lignocellulose has generated widespread interest in understanding the biochemistry of lignocellulose degradation which is carried out by one of the copper containing oxidative enzyme namely Laccase. These enzymes are present in all organisms which are involved in lignocellulose degradation but their copper binding sites in the respective amino acid residues are still controversial. In order to overcome this puzzle: sequence analysis was performed in selected lignocellulose degrading fungus namely Aspergillus fumigatus, Aspergillus flavus and Fusarium oxysporum to understand the evolutionary relationship via Multalign, Phylogeny.fr and MetalDetector. This study reveals the evolutionary relationship of Laccase in the above fungal sps., involved in lignocellulose degradation clearly shows: evolution pattern of Laccase in selected fungus with high bootstrap value. A.Flavus Laccase which holds the molecular weight of 65706.2 Da is the ancestor for subsequent evolution of Laccase in other fungal sps and it Metal binding residues identification to enhance the Laccase activity in selected microorganisms against organic waste contaminant area and to increase the process of lignocellulose degradation towards biofuel, composting and bioremediation or Solid waste management applications.